THE IMPORTANCE OF C-REACTIVE PROTEIN IN DISCOGENIC LOW BACK PAIN: THE ANALYSIS OF 444 PATIENTS - Durdağ, Emre; Albayrak, Serdal; Atcı, İbrahim Burak; Çivi, Soner; Kardeş, Özgür; Koca, Suleyman Serdar (My University, 2018)
Background: Low back complaint is the most common health problem. Recent studies point out the role of inflammation on discogenic back pain. In this study, we intended to examine the importance of C-reactive protein (CRP) level in discogenic low back pain.Material and Methods: 444 patients with discogenic low back pain were assessed in three groups. The first group (n=229) consisted of patients who appealed to outpatient clinic and who were recommended medical therapy. In the second group (n=15), there were patients who appealed to outpatient clinic and who were offered operation but who did not accept surgery. As for the third group (n=200) included patients who were operated because of single level lumbar discopathy. All patients were assessed in terms of CRP positivity at the first admission and whether surgery is recommended or not.Results: Positivity of CRP was significantly higher in the group to whom surgery is recommended (n=215) than in medical treatment recommended patients (17.8 % vs. 3.1%, p < 0.0001, OR=6.8, 95 % CI: 2.9-15.6). Furthermore, the positivity of CRP was found significantly higher in the third group compared to the first group (18 % vs. 3.1 %, p < 0.0001, OR= 6.9, 95 % CI: 3.1-16.1). However, it was relatively higher in the second group than in the first group (13.3 % vs. 3.1 %, p=0.0626, OR=4.9, 95% CI: 0.9-25.9).Conclusion: Discogenic low back pain is caused by both mechanical and inflammatory factors. Preoperative CRP values can be predictive for inflammatory process in lomberdiscopathy. For more accurate results further studies are needed.
Keywords: Romatoloji